Association Between Dietary Patterns and Nutritional Status of Fifth-Grade Students in Kediri District - Baiq Nurul Azizah; Kusmiyati Kusmiyati; Dewa Ayu Citra Rasmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The quality of future human resources is closely linked to the current nutritional status of children. Unhealthy and irregular dietary patterns can lead to undernutrition or overnutrition, affecting overall health and brain development. This study aimed to examine the relationship between dietary patterns and the nutritional status of fifth-grade students in Kediri District. A correlational design with random sampling was conducted in eight schools, involving 221 respondents. Dietary patterns were classified as good (66.5%), fair (24.4%), very good (7.2%), and poor (1.8%). Nutritional status was predominantly normal (96.8%), with 3.2% categorized as overweight, and no cases of underweight. Chi-Square analysis indicated a significant association between dietary patterns and nutritional status (p = 0.009 < 0.05), with a low correlation coefficient (r = 0.224). These findings suggest that dietary patterns are not the sole determinant of nutritional status; factors such as health condition, physical activity, illness frequency, and environmental conditions also contribute. It is recommended to promote healthy eating habits among students and parents, ensure food hygiene in schools, and provide nutritious food options. Future research should consider nutritional education interventions to assess their impact on students’ dietary patterns and nutritional status.